Association of non-alcoholic fatty liver disease and all-cause mortality in hospitalized cardiovascular disease patients: A systematic review and meta-analysis - Surasak Saokaew (2022)
BACKGROUND: Controversy remains concerning the association of the all-cause mortality risk of hospitalized cardiovascular disease (CVD) patients with non-alcoholic fatty liver disease (NAFLD). This study investigated the risks of all-cause mortality among hospitalized CVD patients with NAFLD. METHODS: We used related keywords to search for studies in 3 electronic databases: PubMed, EMBASE, and Cochrane Library. All eligible studies published up to April 2020 were reviewed. The findings of those studies reporting the mortality outcomes of hospitalized CVD patients with and without NAFLD were examined, and the various study results were pooled and analyzed using a random-effects model. A quality assessment using the Newcastle-Ottawa scale was performed on the studies selected for inclusion in a meta-analysis. RESULTS: A total of 2135 studies were found, of which 3 were included in this meta-analysis. All studies were considered good quality. The mean age of the patients in the analysis was 73 years, and about half of them were men. The comorbidities reported were hypertension, diabetes mellitus, and dyslipidemia. The results showed that hospitalized CVD patients with NAFLD were at a significantly higher risk of all-cause mortality than non-NAFLD patients (adjusted hazard ratio of 2.08 [95% confidence interval, 1.56-2.59], P < .001). The included studies showed low heterogeneity (I2 = 0.0%, P = .473), and Begg and Egger tests revealed no apparent publication bias (P = .327 and P = .682, respectively). CONCLUSIONS: Hospitalized CVD patients with NAFLD were at a higher risk of all-cause mortality than those without NAFLD. More studies that further explore this association are needed.